The multinational nature of cost-effectiveness analyses alongside multinational clinical trials. - Rivero-Arias, O; Gray, A (Elsevier, 2010)
OBJECTIVES: Applied and methodological evidence to the conduct of economic evaluations alongside multinational clinical trials have appeared in the literature over the last decade. Nevertheless, little is known about the number and identity of countries participating in these studies. A structured review was carried out to assess the reporting of the multinational nature of these studies. METHODS: A structured review was conducted by using online databases from January 1996 to December 2007. Articles were included if they reported cost-effectiveness analysis alongside a multinational randomized trial with individual patient-level data on resource use and outcome in more than one country. Key data extracted included country information, sample size, unit cost collection, methods to calculate costs and effects, and the reporting of incremental cost-effectiveness ratios. RESULTS: Sixty-five studies out of a total of 591 articles identified in the original search fulfilled the inclusion criteria and were included in the review. Information about countries participating in the trial was not reported in 16 (26%) of the 65 studies. The overall sample size from all the randomized controlled trials identified was estimated to be 172,401 patients. Country-specific sample size was reported for 74,852 (43%) of the patients, but the country contribution was unknown for 97,549 (57%) of the participants. CONCLUSION: The reporting of the multinational nature of these studies is currently inadequate. Therefore, future guidelines of transferability of economic evaluations across settings should emphasize the importance of reporting the number and identity of countries and their contribution to the overall sample size in cost-effectiveness analyses alongside multinational clinical trials.